Composition formulas of Fe-based transition metals-metalloid bulk metallic glasses derived from dual-cluster model of binary eutectics - Gul Jabeen Naz (Nature Portfolio, 2017)
Abstract It is known that bulk metallic glasses follow simple composition formulas [cluster](glue atom)1 or 3 with 24 valence electrons within the framework of the cluster-plus-glue-atom model. Though the relevant nearest-neighbor cluster can be readily identified from a devitrification phase, the glue atoms remains poorly defined. The present work is devoted to understanding the composition rule of Fe-(B,P,C) based multi-component bulk metallic glasses, by introducing a cluster-based eutectic liquid model. This model regards a eutectic liquid to be composed of two stable liquids formulated respectively by cluster formulas for ideal metallic glasses from the two eutectic phases. The dual cluster formulas are first established for binary Fe-(B,C,P) eutectics: [Fe-Fe14]B2Fe + [B-B2Fe8]Fe ≈ Fe83.3B16.7 for eutectic Fe83B17, [P-Fe14]P + [P-Fe9]P2Fe≈Fe82.8P17.2 for Fe83P17, and [C-Fe6]Fe3 + [C-Fe9]C2Fe ≈ Fe82.6C17.4 for Fe82.7C17.3. The second formulas in these dual-cluster formulas, being respectively relevant to devitrification phases Fe2B, Fe3P, and Fe3C, well explain the compositions of existing Fe-based transition metals-metalloid bulk metallic glasses. These formulas also satisfy the 24-electron rule. The proposition of the composition formulas for good glass formers, directly from known eutectic points, constitutes a new route towards understanding and eventual designing metallic glasses of high glass forming abilities.